The technical potential of Great Britain to produce ligno‐cellulosic biomass for bioenergy in current and future climates. Issue 2 (1st November 2013) - Hastings, Astley; Tallis, Matthew J.; Casella, Eric; Matthews, Robert W.; Henshall, Paul A.; Milner, Suzanne; Smith, Pete; Taylor, Gail
Abstract Process and empirical‐based models that describe lignocellulosic biomass yield of the perennial energy grass Miscanthus (MiscanFor©), short rotation coppice (SRC) trees and shrubs, poplar and willow (ForestGrowth‐SRC) and a number of short rotation forest trees (ESC‐CARBINE), were used to estimate the yield potential for current and future climates across Great Britain (GB). In current climates, modelled yields for all feedstock crops varied between 8.1 and 10.6 Mg dry weight (DW) ha−1 yr−1 with willow SRC and poplar SRF producing the lowest and highest yields respectively. For the medium emissions scenario (UKCP09) in 2050, mean yield for all feedstock crops varied between 7.6 and 12.7 Mg DW ha−1 yr−1 with willow SRC and poplar SRF once again the lowest and the highest recorded yields. There were clear geographical trends within GB. Miscanthus yield was higher than all others in the south‐west (13.1 Mg DW ha−1 yr−1), SRC willow and SRC poplar in the north‐west (12.1–15.8 Mg DW ha−1 yr−1) and in the midlands and south‐east, SRF poplar was the highest yielding (10.5–11.6 Mg DW ha−1 yr−1). These geographical trends changed little with climate out to 2050, with mean yield of each 'best feedstock' increasing from 12.7 to 14.2 Mg DW ha−1 yr−1. Out to 2050, SRC declined slightly and Miscanthus and SRF poplar increased as the 'best feedstock' option. Except for a few localized examples, only SRF poplar had a higher yield than SRC or Miscanthus. These data suggest that in current and future climates, lignocellulosic biomass plantation species can be selected and optimized for best yield performance in different regions of GB. This modelling framework provides a valuable starting‐point for which to test the performance of new genetic material, as this becomes available and parameterized for the models and socio‐economic scenarios that may impact on the bioenergy industry.